Neural signature on easy to difficult level of N-back working memory load tasks in healthy subjects - a study of cognitive processing using EEG - Ismail, Kartina (2021)
INTRODUCTION: Issue in cognitive process is linked with deficit of working memory. The purpose of this study is to assess the neural processing during easy to difficult level of n-back working memory load task in healthy subjects from EEG data. METHODOLOGY: 28 healthy subjects (25 male, 3 female) who have completed at least nine years of education were involved in the experiment. They were required to complete four level of working memory load task which level as easy (0-back to 1back), moderate (2-back) and difficult (3-back). Instructions were provided before each task start. Cross-sectional design with convenient sampling was applied in the study. EEG was recorded using ANT Neuro 64-channel. Data was collected with participant consent form and pre-processing was done in Besa Research 6.1 software. The processed data then analyse with one-way ANOVA and Friedman test where p < 0.05. RESULTS: Theta oscillation shows it was statistically difference in frontal [F (3,108) = 10.91, p = 0.000], central [F (3,108) = 14.11, p = 0.000], left temporal [F (3,108) = 5.24, p = 0.002], right temporal [F (3,108) = 4.09, p = 0.009], parietal [F (3,108) = 3.83, p = 0.012] and occipital [F (3,108) = 4.40, p = 0.026]. Additionally, central theta indicated 0- back was statistically significant difference in all conditions of n-back working memory load task (p < 0.05). There was only certain n-back working memory load task show statistically mean difference in another region. Gamma shows statistically difference between 0-back and the increase level of n-back working memory load tasks, 2(23) 296.962, p <0.000. Bonferroni correction revealed that gamma was statistically difference in the right temporal on 0-back with 1-back (p=0.016), 2-back (p = 0.023) 3-back (p=0.030) and left temporal on 0-back with 3-back (p=0.009). All other regions do not show any significant finding for gamma oscillations apart from the two regions of left and right temporal. CONCLUSION: The EEG results generally indicated that increase of working memory load influences the decline of theta oscillatory whereas gamma oscillation occurs in two regions with specified working memory load task condition. Thus, the study presented the role of WM component such as attention, inhibition and recall in healthy adults.